2014
DOI: 10.1007/s10237-014-0612-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone’s responses to different designs of implant-supported fixed partial dentures

Abstract: This paper explores the biomechanics and associated bone remodeling responses of two different abutment configurations, namely implant-implant-supported versus tooth-implant-supported fixed partial dentures. Two 3D finite element analysis models are created based upon computerized tomography data. The strain energy density induced by occlusal loading is used as a mechanical stimulus for driving the bone remodeling. To measure osseointegration and stability during healing, a resonance frequency analysis is cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…An adaptive bone remodeling simulation has been developed to quantitatively predict the bone response after implantation. The previous studies have showed a good agreement of bone remodeling simulated results and animal/clinical experiments (Lin et al 2009b;Rungsiyakull et al 2015). Thus, the conclusion drawn from a bone remodeling simulation study may be more clinically relevant.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…An adaptive bone remodeling simulation has been developed to quantitatively predict the bone response after implantation. The previous studies have showed a good agreement of bone remodeling simulated results and animal/clinical experiments (Lin et al 2009b;Rungsiyakull et al 2015). Thus, the conclusion drawn from a bone remodeling simulation study may be more clinically relevant.…”
Section: Introductionmentioning
confidence: 78%
“…Strain energy density (SED) was used as the bone remodeling signal, with a homeostatic level of K ref = 0.0036 J/(g/mm 3 ) (Lin et al 2010b). The lazy zone, where no change in bone properties occurred, spanned ±10 % of this value δ (Rungsiyakull et al 2015). If the calculated strain energy density was over 10 % higher than K ref , the density and modulus were predicted to increase by the algorithm; if the strain energy density was more than 10 % lower than K ref , the tissue was predicted to resorb and the modulus decreases.…”
Section: Bone Remodeling Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDL cushions the abutment teeth from direct contact with the cortical and cancellous bone that form the bone sockets . The T‐FPD model preparation involved partial/full removal of the occlusal tissue on the abutment teeth . Some special considerations were taken in the modeling for determining the taper angle of abutment teeth to reflect the clinical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…2012), a regular grid to simplify the bone microstructure (Brown 2013), and perfect bonding between the screw and the bone (Wirth et al. 2012a, b; Rungsiyakull 2015). Moreover, the screw insertion operation itself is likely to induce micro-fractures in the bone structure that may substantially lower the bone’s mechanical performance (Yadav 2012; Wang 2014), something that has not been taken into consideration in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%